PENGEMBANGAN SISTEM INFORMASI KEPEGAWAIAN (SIMPEG) BERBASIS WEB - Teddy Marliadi Nurwan (Journal Of Regional Public Administration (JRPA), 2019)
The author's purpose in writing this article is to evaluate, look for obstacles and efforts to implement a web-based Information System in Sukatali Village that is able to present information so that it can be accessed via the internet. In this study, researchers used a method of collecting literature and field study data consisting of observations, and interviews in the sub-division of the Sukatali village staffing department. Administrators and central admins can find out employees who will be promoted, raise salaries periodically, and retire according to the period, do a promotion of Decree SK Promotion, Periodic Increase Salary Decree, and Pension Proposal automatically, which was previously done manually. Work Unit Admins can find out employees in their work units who move upward, raise periodic salaries and retire through the report module. Employees can pr int a curriculum vitae, Decree of Promotion, Decree on Increase of Salary Period and Pension Proposal owned. Based on the conclusions that have been put forward, several suggestions for further development can be proposed including the development of staffing information systems with the addition of leave modules, and transfer. Development of SIMPEG On Web with features of making SK that is customizable. Development of SIMPEG Sukatali Village that can be integrated with the State Personnel Agency (BKN).